The Interplay between Oxidative Stress, Exercise, and Pain in Health and Disease: Potential Role of Autonomic Regulation and Epigenetic Mechanisms - Jolien Hendrix; Jo Nijs; Kelly Ickmans; Lode Godderis; Manosij Ghosh; Andrea Polli (MDPI AG, 2020)
Oxidative stress can be induced by various stimuli and altered in certain conditions, including exercise and pain. Although many studies have investigated oxidative stress in relation to either exercise or pain, the literature presents conflicting results. Therefore, this review critically discusses existing literature about this topic, aiming to provide a clear overview of known interactions between oxidative stress, exercise, and pain in healthy people as well as in people with chronic pain, and to highlight possible confounding factors to keep in mind when reflecting on these interactions. In addition, autonomic regulation and epigenetic mechanisms are proposed as potential mechanisms of action underlying the interplay between oxidative stress, exercise, and pain. This review highlights that the relation between oxidative stress, exercise, and pain is poorly understood and not straightforward, as it is dependent on the characteristics of exercise, but also on which population is investigated. To be able to compare studies on this topic, strict guidelines should be developed to limit the effect of several confounding factors. This way, the true interplay between oxidative stress, exercise, and pain, and the underlying mechanisms of action can be revealed and validated via independent studies.